2017
DOI: 10.1080/02699052.2017.1385853
|View full text |Cite
|
Sign up to set email alerts
|

The effects of tackle height on inertial loading of the head and neck in Rugby Union: A multibody model analysis

Abstract: Although further model validation is required, the results of this study indicate the need for further research on tackle heights and inertial head-and-neck loading in the tackle phase of play in Rugby Union.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 37 publications
0
47
0
Order By: Relevance
“…Tackles were categorised as either upper body tackles which are defined by the tackler's intended primary contact being above the ball carrier's hip or lower body tackles defined by intended primary contact being at or below the ball carrier's hip (Tierney, Lawler, et al, 2016;Tierney & Simms, 2017a, 2017b. Tackles were also categorised as either front-on or side-on tackles.…”
Section: Research Design and Data Collectionmentioning
confidence: 99%
“…Tackles were categorised as either upper body tackles which are defined by the tackler's intended primary contact being above the ball carrier's hip or lower body tackles defined by intended primary contact being at or below the ball carrier's hip (Tierney, Lawler, et al, 2016;Tierney & Simms, 2017a, 2017b. Tackles were also categorised as either front-on or side-on tackles.…”
Section: Research Design and Data Collectionmentioning
confidence: 99%
“…9 Although the long term medical outcome of this case is unknown, these results support the finding that legal shoulder tackles to the upper trunk where the ball carrier is visually unaware is a concern for inertial head loading. 30 A conclusion regarding injury risk associated with these tackles requires correlation with injury data and this 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 should be a focus of future work. Longitudinal studies considering blood biomarkers, medical imaging, concussion history, medical reports, injury data and overall head impact exposure would be of benefit.…”
Section: Discussionmentioning
confidence: 99%
“…inertial head kinematics as a result of an impact to the body) for which lower frequency head motion is typically associated with. 30 In this case, matching was conducted on synchronised video of three camera views of the tackle. Each video had a resolution of 720p and frame rate of 25 fps.…”
Section: Methodsmentioning
confidence: 99%
“…An alternative approach is to use multibody modelling. Multibody models have been used to study head kinematics during concussive direct-head impacts in unhelmeted sports including rugby union and Australian rules football [4][5][6] as well as inertial head loading during legal rugby union tackles [7]. McIntosh et al [6] used a passive MADYMO (TASS International, Helmond, Netherlands, 2015, Version 7.6) facet human body model approach to calculate six degree-of-freedom head kinematics from concussive and non-concussive direct head impacts in unhelmeted sports.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that angular acceleration of the head in the coronal plane had the greatest association with a concussion, with tentative threshold values of 1747 rad/s 2 and 2296 rad/s 2 reported for a 50% and 75% chance of concussion, respectively. Tierney and Simms [7] recently used the MADYMO passive ellipsoid multibody human body model and demonstrated that tackles to the upper body can cause greater inertial head and neck loading than tackles to the lower body, particularly for the ball carrier. They also postulated that tackles to the upper body may be a catalyst for some of the chronic head and neck symptoms exhibited by a rugby player.…”
Section: Introductionmentioning
confidence: 99%